Ficções das masculinidades: a representação do gay em Pai, pai de João Silvério Trevisan - Joney Fonseca Vieira (2021)
This research investigates and discusses gay representation in contemporary brazilian Gay Literature. Starting from the reflection on the book Pai, pai (Father, father) written by João Silvério Trevisan who, through autobiographical writing, tries to rescue his absent father and still search for himself, the man in constant exile for being homossexual, the work has as its main objective the analysis of the ways in which the gay character appears in literature. In the last three decades in Brazil, LGBTQIA+ community, despite recent setbacks that attempt against democracy and against social diversity, has reached considerable advances in the fields of politics, education, health and others. Among the agents promoting reflections on the reality of these social groups, and their representation in the artistic field, are Literary Studies. So, from homossexual characters described as examples of human kinds – medical and social phenomena – to gay characters who express their feelings and share their livings, there is a process of academic production, still in a pioneering stage, whose research and publications have provoked discussions around the existence of a LGBTQIA+ Literature and its constitutive elements such as its authors, its audience, its aesthetic variations and, consequently, as another aspect to be explored by publishing market. The theoretical-methodological contribution that underlies the research encompasses elements of the representation of the gay subject, the Freudian psychoanalytic analysis to examine the relationship between heterosexual father and gay son, and also through the scope of fictionalized autobiography - self-fiction. So, this dissertation intends to promote reflections on arguments and counter-arguments enunciated by the Theory of Literature, in addition to recognizing the historical importance of already established literary aesthetics, to appropriate the construction of this Gay Literature and, in this proposal, to avoid relativization of discourses and concepts that form stereotypes reducing people whose sexual orientation or gender identity make them dissident beings.